IMPLEMENTASI METODE PROTOTYPE PADA SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMK STB DEPOK DENGAN TERINTEGRASI WHATSAPP DAN EMAIL - Rizki Hadi; Mochamad Adhari Adiguna (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The presence of computer technology today, in 2022 continues to grow rapidly making the need for human information increase, especially in education so that the education sector must be able to keep up with technological developments, especially computer technology. In the field of education, an academic information system for high school students is a major need for related managers to assist the processing of student academic data so as to produce useful and accurate information. Educational institutions have utilized information systems to encourage students' academic development, one of which is in High School Student Education (SMK). Based on the results of interviews, the STB Vocational School currently does not have an academic information system with WhatsApp and email features, and is unable to record, manage, search, store and present academic information data and student reports (transcripts) are carried out using Microsoft Word and Microsoft Excel so that developmental data students' academics have not been centered on one database. This is less efficient and can occur errors, errors, and the existence of duplicated data in making reports on student progress (Raport). In designing this system using a prototype and web-based model that can shorten the process and time required by using PHP as a programming language and MySQL as a database and using the CodeIgniter Framework, this system can provide information such as academic year data, teacher data, student data, data class. In addition, the data obtained can be more accurate and errors can be avoided.